Codificação de canal para comunicações ultra confiáveis em sistemas 5G - Terças, Leonardo (2019)
Channel coding is nothing more than a technique where redundancy bits are inserted into the message of interest, so that while reception they can be used to detect and correct errors. This technique introduced by Shannon in 1948, has been the subject of several researches that seek to develop and improve good error-correcting codes to achieve the channel capacity predicted by the mathematician. Aiming at fifth generation wireless communication systems (5G), some channel coding techniques have become candidates for use in their transmissions. The objective of this work is to study and compare two codes, convolutional and polar codes, aiming at application in ultra-reliable and short packet communications in 5G systems. Thus, the study of the coders and decoders of these codes and a computational implementation to evaluate their performance was performed. The results show that polar codes perform better in error correction and detection, however they have high latency using the successive cancellation decoder. Convolutional codes, however, perform better in latency, but do not meet expected metrics in error correction and detection.